2000
DOI: 10.1046/j.1439-0450.2000.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-term Oral Administration of an Immunostimulant Diet on Innate Immunity in Sea Bass (Dicentrarchus labrax)

Abstract: Immunostimulants represent a modern and promising tool in aquaculture, enhancing the resistance of cultured fish to disease and stress. This study investigated the effect of a combination of dietary glucans, alpha-tocopherol and ascorbic acid on the innate immune response of cultured sea bass (Dicentrarchus labrax). After 5 weeks of adaptation on a commercial diet containing 100 p.p.m. ascorbic acid and 200 p.p.m. alpha-tocopherol, sea bass were switched to a diet supplemented with 2% beta-1.3/beta-1.6 glucans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
63
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 24 publications
2
63
2
4
Order By: Relevance
“…Studies conducted on different fish species, such as Atlantic salmon (Salmo salar, Linnaeus 1758) [18], rainbow trout (Oncorhynchus mykiss, Walbaum 1792) [15,19,20], spotted rose snapper (Lutjanus guttatus, Steindachner 1869) [21], common carp (Cyprinus carpio, Linnaeus 1758) [16,22,23], roho labeo (Labeo rohita, Hamilton 1822) [13,24], gilthead sea bream (Sparus aurata Linnaeus 1758) [25], sea bass (Dicentrarchus labrax, Linnaeus 1758) [26,27], Nile tilapia (Oreochromis niloticus, Linnaeus 1758) [28], silver seabream (Pagrus auratus, Forster 1801) [12], large yellow croaker (Pseudosciaena crocea, Richardson 184) [29], and southern bluefin tuna (Thunnus maccoyii, Castelnau 1872) [30] have reported that β-glucans act by modulating different parameters of the immune response and increasing resistance to diseases [8,12]. Therefore, the objective of the present study was to determine the effect of different oral doses of β-1,3/1,6-glucan on growth, survival, digestive enzymatic activity, and the expression of several genes associated with the immune system and the intestinal barrier function in juveniles of the tropical gar (A. tropicus).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted on different fish species, such as Atlantic salmon (Salmo salar, Linnaeus 1758) [18], rainbow trout (Oncorhynchus mykiss, Walbaum 1792) [15,19,20], spotted rose snapper (Lutjanus guttatus, Steindachner 1869) [21], common carp (Cyprinus carpio, Linnaeus 1758) [16,22,23], roho labeo (Labeo rohita, Hamilton 1822) [13,24], gilthead sea bream (Sparus aurata Linnaeus 1758) [25], sea bass (Dicentrarchus labrax, Linnaeus 1758) [26,27], Nile tilapia (Oreochromis niloticus, Linnaeus 1758) [28], silver seabream (Pagrus auratus, Forster 1801) [12], large yellow croaker (Pseudosciaena crocea, Richardson 184) [29], and southern bluefin tuna (Thunnus maccoyii, Castelnau 1872) [30] have reported that β-glucans act by modulating different parameters of the immune response and increasing resistance to diseases [8,12]. Therefore, the objective of the present study was to determine the effect of different oral doses of β-1,3/1,6-glucan on growth, survival, digestive enzymatic activity, and the expression of several genes associated with the immune system and the intestinal barrier function in juveniles of the tropical gar (A. tropicus).…”
Section: Introductionmentioning
confidence: 99%
“…Absorption of peptides is considered as a major route of transport in the intestine of vertebrates, and small peptides are absorbed faster than free amino acids (Adibi, 1997;Tesser et al, 2005). In aquaculture, immunostimulants were considered as a promising tool to enhance the resistance of cultured fish to disease and stress (Bagni et al, 2000). And some commercial feed supplements with immunostimulating capacities have already been applied (Cook et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Sea bass fed with 2% MacroGard for 2 weeks every 3 months showed increased serum complement 564 activity and plasma lysozyme activity at the end of 3 cycles [195]. Further studies have shown that 565 MacroGard at 0.1% for 15 days also increased serum complement activity, serum lysozyme activity and 566 gills HSP70 content at 30 days from the end of the treatment period.…”
mentioning
confidence: 90%
“…Sea bass fed with 2% MacroGard for 2 weeks every 3 months showed increased serum complement 564 activity and plasma lysozyme activity at the end of 3 cycles [195]. Further studies have shown that…”
mentioning
confidence: 95%